Submission from the Consortium of International Agricultural Research Centers, to UNFCCC SBSTA 44 on issues related to agriculture in response to SBSTA decision FCC/SBSTA/2014/L.14. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Identification and assessment of agricultural practices and technologies to enhance productivity in a sustainable manner, food security and resilience, considering the differences in agro-ecological zones and farming systems, such as different grassland and cropland practices and systems.